Formation control of multi-agent systems : a graph rigidity approach - Queiroz, Marcio S. de; Cai, Xiaoyu, 1987-; Feemster, Matthew (John Wiley & Sons, Inc., 2019)
Uses the concept of graph rigidity as the basis for describing the multi-agent formation geometry and solving formation control problems. Considers different agent models and formation control problems. Control designs throughout the book progressively build upon each other. Provides a primer on rigid graph theory. Combines theory, computer simulations, and experimental results Market description: Primary: Researchers and practitioners working in the areas of control systems, robotics and multi-agent systems. Secondary: Graduate students in control systems, robotics, and multi-agent systems"- Resumé vydavatel
Keywords: multiagentní systémy; teorie grafů; automatické řízení; matematické modely; robotika; multi-agent systems; graph theory; automatic control; mathematical models; robotics; elektronické knihy; monografie; electronic books; monographs